Can message framings influence air passengers' perceived credibility of aviation voluntary carbon offsetting messages?. Issue 9 (2nd September 2019) - Zhang, Beile; Ritchie, Brent; Mair, Judith; Driml, Sally
Abstract: Past literature has identified low purchase rates of aviation voluntary carbon offsetting (VCO) schemes. A lack of credibility of such schemes has been identified as a key obstacle, yet little attention has been given on how to enhance perceived credibility. Using communication theory, this study examines effects of message framing on consumers' perceived credibility of aviation VCO messages. Data were drawn from a representative sample of 1680 Australians. The results revealed that spatial distance framing influences air passengers' perceived credibility of aviation VCO messages. Messages focusing on the influence of VCO programs on the environment of a local community obtain higher perceived credibility than those located in other countries. The study also found the interaction of spatial and temporal distance framing effects were different based on consumers' past purchase experience. The findings suggest how airlines should design messages and refine them based on consumers' past experience of aviation VCOs.